Bridging Indigenous and Western sciences in freshwater research, monitoring, and management in Canada. Issue 3 (12th July 2021) - Alexander, Steven M.; Provencher, Jennifer F.; Henri, Dominique A.; Nanayakkara, Lushani; Taylor, Jessica J.; Berberi, Albana; Lloren, Jed Immanuel; Johnson, Jay T.; Ballard, Myrle; Cooke, Steven J.
Abstract: Mutually respectful and reciprocal relationships between people and their environment is a central tenet of many Indigenous worldviews. Across the Americas, this relational connection is particularly evident when it comes to freshwater ecosystems. However, there are numerous threats to these central relationships between Indigenous peoples and their environment. Using all available ways of knowing to conserve, prioritize, and restore relationships between Indigenous peoples and the environment they live in, and are a part of, is critical. Despite legislative requirements and policy commitments, developing and implementing inclusive approaches that bridge multiple ways of knowing remains a challenge. This systematic map examines the extent, range, and nature of published case studies that seek to bridge Indigenous and Western sciences in ecological research, monitoring, or natural resource management across Canada's freshwater aquatic ecosystems. A total of 74 Canadian case studies from 72 articles were included in the systematic map. There were 30 distinct species of focus across the collection of case studies. This systematic map highlights the diversity of ways knowledge systems can be woven, but that the application of these approaches is limited to some key regions (the Pacific and northern regions) and species (whitefish and salmon). The extent and nature of information provided with regards to demographics (e.g., gender, age) of Indigenous knowledge holders contributing to the studies varied widely and in general was poorly reported. Across all of the case studies included in the systematic map there were 78 distinct Indigenous knowledge systems represented. Fifteen different methodological approaches were identified with community‐based participatory research being the most prevalent approach. The presence and diversity of Indigenous methodologies employed was also notable and was greater as compared to a previous study of Canada's coastal marine regions. Collectively, these findings point to a potential emerging transformation in research focused on freshwater ecosystems, habitats, and species to a practice that elevates the role of Indigenous communities, centres Indigenous science and knowledge, and is informed by Indigenous ways of being and doing. Abstract : This systematic map, which includes 74 published case studies, highlights the diversity of ways knowledge systems can be woven. Furthermore, our findings point to a potential emerging transformation in research focused on freshwater ecosystems, habitats, and species to a practice that elevates the role of Indigenous communities, centers Indigenous science and knowledge, and is informed by Indigenous ways of being and doing. Résumé: Le maintien de relations mutuellement respectueuses et réciproques entre les peuples et leur environnement sont un principe central de nombreuses visions du monde autochtones. Dans les Amériques, ce lien relationnel est particulièrement évident lorsqu'il s'agit des écosystèmes d'eau douce. Cependant, de nombreuses menaces pèsent sur ces relations centrales entre les peuples autochtones et leur environnement. Il est essentiel d'utiliser tous les modes de savoirs à notre disposition pour préserver, prioriser et restaurer les relations entre les peuples autochtones et l'environnement dans lequel ils vivent et dont ils font partie intégrante. En dépit des exigences législatives et des engagements politiques, l'élaboration et la mise en œuvre d'approches inclusives qui allient de multiples modes de savoirs demeurent un défi. Cette carte systématique porte sur l'étendue, la gamme et la nature des études de cas publiées qui visent à mettre en commun les sciences autochtones et les sciences occidentales dans la recherche et la surveillance écologiques ou la gestion des ressources naturelles portant sur les écosystèmes d'eau douce du Canada. Au total, 74 études de cas canadiennes provenant de 72 articles ont été incluses dans la carte systématique. La compilation des études de cas comportait 30 espèces distinctes. Cette carte systématique met en évidence la diversité des façons dont les systèmes de savoirs peuvent être tissés, mais aussi le fait que l'application de ces approches est limitée à certaines régions clés (les régions du Pacifique et du Nord) et à certaines espèces (le corégone et le saumon). En ce qui concerne les données démographiques (p. ex. le sexe et l'âge) des détenteurs de savoirs autochtones contribuant aux études, l'étendue et la nature des informations fournies variaient considérablement et étaient, en général, faiblement documentées. Les études de cas figurant dans la carte systématique représentent 78 systèmes de savoirs autochtones distincts. Quinze approches méthodologiques différentes ont été répertoriées, la plus répandue étant la recherche participative communautaire. La présence de méthodologies autochtones et leur diversité sont également notables, car elles étaient plus nombreuses que dans une précédente étude portant sur les régions marines et côtières du Canada. Collectivement, ces résultats indiquent une potentielle transformation de la recherche axée sur les écosystèmes, les habitats et les espèces d'eau douce vers une pratique qui met en valeur le rôle des communautés autochtones, qui privilégie la science et le savoir autochtones, et qui est éclairée par les manières d'être et de faire des Autochtones.